DARI DESA UNTUK ENERGI: MEMERIKSA DAMPAK KEPEMIMPINAN PEREMPUAN LOKAL PADA PENGELOLAAN SUMBER DAYA ALAM DI BOJONEGORO - agustina, Ria; Septian, Esa; Suhindarno, Heny (Universitas Bina Taruna Gorontalo, 2025)
This study aims to investigate the transformational leadership style adopted by local women leaders in the face of a changing environment, seeing how their expertise in utilizing existing natural resources. Gender stereotypes are one of the factors in the absence of women leaders in the public sphere. This study applied a qualitative research method with a descriptive approach. Data collection used direct observation techniques, face to face interviews, and event documentation. The results showed that: 1) Ideal influence, Mojodelik Village Head is a charismatic leader and a role model for his subordinates, 2) Inspirational motivation, Mojodelik Village Head always provides support and meets the needs of his subordinates, 3) Individual Attention, Mojodelik Village Head always takes a personal approach and establishes effective communication with subordinates, 4) Intellectual Stimulus, Mojodelik Village Head is able to face existing problems with a future-oriented and able to encourage team creativity so as to create innovation. In the end, the transformational leadership adopted by women has had a positive influence.